2016
DOI: 10.1108/bepam-04-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

A critical success model for PPP public housing delivery in Ghana

Abstract: Purpose – The nature and characteristics of critical success factors (CSFs) that influence success on public private partnership (PPP) arrangements on different project typologies vary between countries and regions. Studies confirm the lack of success on PPP approach on public housing project (PHP). The main challenge to PPP-PHP success has been identifying, analysing, categorizing and matching CSFs that are likely to influence the PPP-PHP outcome. The purpose of this paper is to identify the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 19 publications
2
88
0
2
Order By: Relevance
“…Studies have shown that a relationship can be established between the “ends” and “the means to the ends” of a project (Cserhati & Szabo, ; Kwofie, Afram, & Botchway, ). In Kwofie, Afram, and Botchway (), on developing a critical success model for PPP public housing delivery in Ghana, CSC as the ends were considered as the dependent variables while success factors (the means) were the independent variables. Among the project “ends,” in their study, include satisfaction of parties, delivering affordable houses, quality housing, and timely delivery of project within budget.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that a relationship can be established between the “ends” and “the means to the ends” of a project (Cserhati & Szabo, ; Kwofie, Afram, & Botchway, ). In Kwofie, Afram, and Botchway (), on developing a critical success model for PPP public housing delivery in Ghana, CSC as the ends were considered as the dependent variables while success factors (the means) were the independent variables. Among the project “ends,” in their study, include satisfaction of parties, delivering affordable houses, quality housing, and timely delivery of project within budget.…”
Section: Resultsmentioning
confidence: 99%
“…The “means to the ends” include provision of guarantees by governments, right project identification and project technical feasibility, competitive and transparent procurement process, stable macroeconomic environment, and efficient and effective financial market. The project ends were measured as a composite dependent variable and then linked in a regression equation to identify the “means to the ends.” Though the study by Kwofie et al () established this link based on the supply aspect of affordable housing, not much studies exist on the demand and supply perspective for the household and developers, respectively. Besides, a comprehensive index can be developed from the identified criteria in this study to measure success from the perspective of both the household and developers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the important role of private sector, the "PPP ideology" has been seen as a strategy to provide affordable housing without adding public debt and actively explored by scholars in this field from all over the world. For instance, Kwofie et al (2016) identified the critical success factors that influence PPP public housing delivery in Ghana [21]. Guarini and Battisti (2017) established a feasibility assessment model for social housing PPP project in Italy [22].…”
Section: Ppp Ideology For Affordable Housing Financingmentioning
confidence: 99%